2011
DOI: 10.1088/1674-4926/32/4/045001
|View full text |Cite
|
Sign up to set email alerts
|

Multimode high-resolution DPWM for RF class-D amplifiers

Abstract: This paper describes a multimode high-resolution digital pulse width modulator. This modulator, based on a novel hybrid structure, not only has a programmable duty cycle but also realizes phase modulation. A 576 ps pulse resolution is achieved based on a 13.56 MHz switching frequency for near field communication. Fabricated in a SMIC 0.18-m EEPROM CMOS process, the total area of modulator is only 130 180 m 2 . Measurement results validate the multi-mode modulation function and high pulse resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…To obtain the tissue's intrinsic fluorescence spectrum for characteristic analysis, some researchers employed the use of diffuse reflectance spectrum to correct for the effects of absorption and scattering [20,21]. Building upon the dual-band tissue fluorescence spectrum recovery method, this study introduces an excitation-emission spectrum recovery method, as shown in Equation (1).…”
Section: The Dual-band Wavelength Excitation-emission Spectrum Recove...mentioning
confidence: 99%
“…To obtain the tissue's intrinsic fluorescence spectrum for characteristic analysis, some researchers employed the use of diffuse reflectance spectrum to correct for the effects of absorption and scattering [20,21]. Building upon the dual-band tissue fluorescence spectrum recovery method, this study introduces an excitation-emission spectrum recovery method, as shown in Equation (1).…”
Section: The Dual-band Wavelength Excitation-emission Spectrum Recove...mentioning
confidence: 99%